Pengaruh Stimulus Mobile Legends terhadap Keterampilan Sosial Remaja di Kelas VIII SMP Negeri 74 Jakarta - Aditya Bimo Prasetyo; Budiaman Budiaman; Martini Martini (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This study aims to determine the effect of mobile legends stimulus on adolescent social skills in grade VIII of SMP Negeri 74 Jakarta. This study uses a quantitative method with a survey method through a questionnaire measured by the ratio scale and the Likert scale. This study uses a quantitative method with a purposive sampling technique. The research was conducted on the condition that the respondents were teenagers who played mobile legends and 8th grade students. The sample obtained amounted to 70 students out of a total population of 280 students. All instruments have been tested using product moment correlation and reliability using alpha cronbach, and have passed the prerequisite test. Data analysis using t-test and large percentage influence using R Square determination coefficient. The results of the study show that (1) there is a significant influence of mobile legends stimulus on social skills, as evidenced by the tcount value of > table, which is 4.163 > 1.995 and Sig < 0.05, which is 0.000 < 0.05. (2) The influence of the R square determination coefficient is 20.3% which is included in the low category and the rest is the influence of other variables outside the variables used.